Drone Detection Sensor With Continuous 2.4 GHz ISM Band Coverage Based on Cost-Effective SDR Platform - Flak, Przemyslaw (IEEE access, 2021)
The development of Unmanned Aerial Vehicles (UAVs), commonly referred to as drones, has introduced revolutionary changes in many areas over the past few years. However, aside from opening new possibilities, the usage of drones in an irresponsible and dangerous manner leads to many hazardous incidents. This paper presents a drone detection sensor with a continuous 2.400 GHz-2.483 GHz operational frequency range for detection methods based on passive radio frequency imaging techniques. The implementation based on Software Defined Radio (SDR) and Field Programmable Logic Array (FPGA) hardware that overcomes the 40 MHz real-time bandwidth limit of other popular SDRs is presented utilizing low-cost off-the-shelf components. Furthermore, a hardware realization of the signal processing chain for specific detection algorithms is proposed to minimize the throughput between SDR and the companion computer and offload software computations. The device validation is made in a laboratory and real-life scenario and presented in relation to the sensor used in other works. In addition to the increased real-time bandwidth, the measurements show a 9 dB reduction in detection sensitivity compared to the reference receiver, in line with the analog RF front-end specifications. The final analysis demonstrates the proposed device's relevance as a sensor for obtaining machine learning datasets and as a part of a final anti-drone system.